2020
DOI: 10.1038/s41415-020-1708-2
|View full text |Cite
|
Sign up to set email alerts
|

The first six weeks - setting up a UK urgent dental care centre during the COVID-19 pandemic

Abstract: A summary is given of how urgent dental care was established in the North East of England during the COVID-19 pandemic, which may help with future preparedness for pandemics.Aerosol generating procedures were almost always avoided in the delivery of urgent dental care. A telephone triage system was effectively used to determine who needed clinical care and to separate symptomatic, asymptomatic and shielding patients, with very few failures in triage noted.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 13 publications
10
51
2
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic has had significant impact upon the provision of medical and dental care globally. In the United Kingdom, routine dental treatment was suspended in late March 2020 [1][2][3][4] , with care instead being provided through a network of urgent dental care centres 5 . During this period, it was advised that aerosol generating procedures (AGPs) were avoided unless absolutely necessary, leading to altered treatment planning and a negative impact on patient care 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has had significant impact upon the provision of medical and dental care globally. In the United Kingdom, routine dental treatment was suspended in late March 2020 [1][2][3][4] , with care instead being provided through a network of urgent dental care centres 5 . During this period, it was advised that aerosol generating procedures (AGPs) were avoided unless absolutely necessary, leading to altered treatment planning and a negative impact on patient care 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high risk of SARS-COV-2 transmissions via dental emergency treatments,the use of therapeutic instruments and equipment has been limited,such as high speed turbines used in pulp treatment,periodontal irrigation for the patientand.The selection of emergency treatment programs was also affected according to the change of the SARS-COV-2 situation.The selection of treatment instruments and equipment was mainly for the treatment of acute symptoms,and the principles of diagnosis and treatment during the SARS-COV-2 are mainly to relieve pain,eliminate in ammation, hemostasis,debridement and suture.In cases of acute Pulpitis (K04.0) and acute apical periodontitis (K04.4),the emergency treatments performed were pulp drainage,or dental pulp inactivation and pulpectomy,hence,these treatment measures as well as medullary pulp cavity disinfection and operation for pain treatments appeared to have increased during the SARS-COV-2.Acute pericoronitis(K05.2) mainly occurs in young people aged 18 to 30 years old [26].During an infection, tooth extraction may lead to the spread of infection and at the same time increases the risk of infection with SARS-COV-2.Therefore,the treatment of acute pericoronitis should be a local treatment,supplemented by Antibiotics and Analgesics drug therapy.For abscess,a small incision is needed for pus discharge and in case of space infection,systemic anti-in ammatory treatment may be necessary [27].The present study showed that trauma accounted for 20.1% during the SARS-COV-2 and although it had decreased from before the SARS-COV-2,it was still the main dental emergency among minors during the SARS-COV-2.Previous studies have shown that children are more likely to suffer trauma [15,28],Parents with children in emergency rooms are more anxious because of SARS-COV-2 [29],Therefore,dentists in charge of dental emergency rooms should be familiar with dental trauma in the primary and mixed dentition.In particular, behavior control is di cult in terms of children with trauma and since guardians can be sensitive and anxious,dentists should be well-trained for the behavioral control of the patient and guardian,their prognosis, and follow-up measures. If necessary,knowledge of drugs and emergency treatment is alsorequired,as pediatric patients may need to be sedated through medication [20,30].During the SARS-COV-2,the emergency treatment principle of trauma was to check the patient's overall condition,whether there was any injury to the brain,chest,abdomen and important organs and to conduct surgical suturing of the injury after excluding any life-threatening conditions [31].…”
Section: Discussionmentioning
confidence: 62%
“…During the SARS-COV-2,dental emergency services experienced an increase in their workload,re ecting the changes in the dental emergency spectrum as the pandemic progressed.The rational allocation of dental professional doctors could compensate for the experienced shortcomings in the dental emergency departments as well as more emergency resources of dental sub-professional doctors could be mobilized [12,15].It would also be necessary to train stomatologists to have solid professional knowledge and surgical skills in dental medicine,in order to meet the technical requirements of potentially encountered dental emergencies and ensure that all conditions can be dealt with quickly and effectively within the emergency department [2,19].At the same time,the dental emergency department should reasonably de ne and adhere to pandemic prevention measures and su ciently stock common anti-in ammatory and analgesic drugs to meet the patients' medical needs.The result may be an improvement in the operation e ciency of emergency treatments in terms of professional technology,personnel and material Distribution of patients by sex,age,day and time…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Where necessary, patients could be referred to urgent dental centre hubs for treatment. 7 This article focuses on a single private practice in England which provides a full range of general and specialist dental treatments. For many years, the clinic has run an effective dental nurse-led triage emergency service seven days a week for their patients.…”
Section: Introductionmentioning
confidence: 99%